Stress biology of cyanobacteria : molecular mechanisms to cellular responses - Srivastava, Ashish Kumar; Rai, A. N. (Amar Nath), 1944-; Neilan, Brett A. (Boca Raton : Taylor & Francis, 2013)
"This reference is a compilation of holistic responses of cyanobacteria ranging from ecology and physiology to modem aspects of molecular biology and biochemistry. It presents research in cyanobacterial stress biologies, from classical to the most modern, and provides a holistic view of cyanobacterial bioenergetics under different abiotic stresses. Authors focus on topics ranging from evolution, ecophysiology, biochemistry, and molecular biology and discuss genomics and proteomics of cyanobacteria under abiotic stresses. Written by a team of global experts from 12 countries, this reference was created for phycologists, marine biologists, chemists, limnologists, botanists, and students of related fields"--
pt. I. Bioenergetics and molecular mechanisms of stress tolerance -- pt. II. Cellular responses and ecophysiology.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Cyanobacteria; Cyanobacteria -- Effect of stress on -- Molecular aspects; Electronic books